The Differences in the Levels of Oxidative Status Marker and Soluble CD95 in Patients with Moderate to Severe COPD during an Exacerbation and a Stable Period. (9th December 2021) - Soodaeva, Svetlana; Kubysheva, Nailya; Klimanov, Igor; Shutov, Alexey; Eliseeva, Tatyana; Novikov, Viktor; Kontorshchikova, Klavdiya; Novikov, Dmitry; Batyrshin, Ildar
Abstract : Studying the features of changes in markers of oxidative stress (OS) and inflammation indicators in COPD patients depending on the degree of bronchial obstruction is one of the priority directions for improving the prognosis and monitoring of the course of this pathology. We conducted a comparative investigation of changes in markers of OS and apoptosis at the systemic and local levels in patients with moderate to severe COPD during exacerbation and stable phase. 105 patients with COPD aged 46-67 and 21 healthy nonsmoking volunteers comparable in age were examined. COPD patients were divided into four groups: moderate COPD (GOLDII) during the exacerbation (GOLDIIex, n = 25 ) and in the stable phase (GOLDIIst, n = 27 ), severe COPD (GOLDIII) during the exacerbation (GOLDIIIex, n = 29 ), and in the stable phase (GOLDIIIst, n = 24 ). We studied the levels of such lipid peroxidation (LPO) products as diene conjugates (DC) and Schiff bases (SB) and parameters of induced chemiluminescence (Imax, total light sum-S, Imax/S) in blood serum, as well as sCD95 concentration in blood and exhaled breath condensate (EBC). The relationship between the values of the OS system indicators with sCD95, as well as with the parameters of lung function, was investigated. Multidirectional changes in OS indicator levels in COPD patients depending on the severity of obstructive airway disorders have been established. The maximum values of DC (0.26 ± 0.046 RU ), Imax (0.265 ± 0.19 RLU), and Imax/S (0.13 ± 0.05 ) were typical for patients with moderate COPD, while the highest SB level (5.7 ± 2.3 RU) was observed in severe COPD during an exacerbation. The exacerbation of the disease was characterized by an increase in DC concentration in both GOLDIIex (0.26 ± 0.046 RU) and GOLDIIIex (0.209 ± 0.02 RU) compared to the stable moderate and severe COPD (0.202 ± 0.028 RU and 0.19 ± 0.03 RU, respectively, p < 0.05 ). The established decrease in high values of DC, Imax, Imax/S, and sCD95 and an increase in SB concentration in GOLD III can serve as quantitative indicators of the prognosis of the severity of the disease. The serum concentration of sCD95 in GOLDIIex (366.4 ± 70.5 U/ml) and GOLDIIst (361.4 ± 72.8 U/ml) did not differ from the control group (393.7 ± 80.9 U/ml, p > 0.05 ). In patients with FEV 1 < 49 % during the exacerbation and stable phase, the serum levels of Imax/S (0.058 ± 0.01 and 0.062 ± 0.01 ) and sCD95 (318.2 ± 66.3 U/ml and 321.4 ± 42.5 U/ml) were lower than the values of healthy volunteers (0.08 ± 0.01 and 393.7 ± 80.9 U/ml, respectively, p < 0.05 ). A positive correlation between sCD95 concentration and airway obstruction degree in all examined COPD patients was established. The revealed numerous associations between sCD95 and OS marker levels in GOLDIII indicate a relationship between systemic radical stress and apoptosis processes both in the respiratory tract and the whole body under conditions of severe inflammation. The established correlations between the values of DC, Imax, and sCD95 in the blood serum and the lung function parameters in all studied patients allow us to consider these indicators as additional prognostic indicators of disease intensification. Our work results help clarify the participation and detail of FRO and apoptosis processes in developing pathophysiological features in moderate to severe COPD in different periods and, accordingly, improve the efficiency of diagnosis and treatment of the disease.